2017
DOI: 10.1039/c6mt00235h
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Cu(ii) on in vitro glycation of human serum albumin by methylglyoxal: a LC-MS-based proteomic approach

Abstract: It has been reported that glycation of human serum albumin (HSA) changes its capability for copper binding whereas the increase of free copper might have an impact on protein glycation - a key process in diabetes progression. In this work, proteomic analysis of non-glycated HSA and HSA glycated with methylglyoxal (MGo) in the absence or in the presence of Cu(ii) (0.1; 1.0; 5.0 mg Cu L) has been undertaken. Trypsin hydrolysates were subjected to capillary HPLC-ESI-QTOF-MS and MS/MS. Raw data were analyzed using… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(2 citation statements)
references
References 41 publications
0
1
0
1
Order By: Relevance
“…In in vitro, proteomics study, it was found that elevated protein glycation might be associated with Cu deficiency and with excessive Cu(II) concentrations [ 52 ]. The data from clinical studies on diabetic patients are contradictory.…”
Section: Discussionmentioning
confidence: 99%
“…In in vitro, proteomics study, it was found that elevated protein glycation might be associated with Cu deficiency and with excessive Cu(II) concentrations [ 52 ]. The data from clinical studies on diabetic patients are contradictory.…”
Section: Discussionmentioning
confidence: 99%
“…В организме концентрации изучаемых металлов вариабельны. Так, физиологические концентрации меди и цинка в сыворотке здоровых людей составляют ~1 мг/л (~15,7 мкМ и ~15,3 мкМ соответственно) [31,32]. В то же время сообщается о значительно более высокой концентрации меди в амилоидных бляшках при болезни Альцгеймера (~400 мкМ) [10,25].…”
Section: Introductionunclassified